Evidence of explosive hydromagmatic eruptions during the emplacement of the North Atlantic Igneous Province - Stokke, E; Liu, E; Jones, M (Volcanica, 2020)
Early Eocene sediments in northwest Denmark contain over 180 well-preserved volcanic ash layers, likely sourced from the North Atlantic Igneous Province (NAIP) between 56.0 and 54.6 Ma. Most of these ashes are basaltic, widespread, and represent a phase of unusually large and explosive eruptions that is coincident with the opening of the northeast Atlantic Ocean. Explosive basaltic eruptions of this magnitude are unheard of in historical times and in the current geological record. Here, we combine analyses of glass sulfur concentrations and variations in morphology and vesicularity of pristine volcanic glass grains to explore the possible eruptive processes promoting such widespread basaltic ash dispersal. We suggest that these ashes formed in shallow subaqueous environments (<200 m water depth) where they fragmented and rapidly quenched during explosive hydromagmatic activity. We speculate that magma-water interaction during the opening of the northeast Atlantic was the main cause of this unusual explosive basaltic activity.